Applications of Magnetotactic Bacteria, Magnetosomes and Magnetosome Crystals in Biotechnology and Nanotechnology: Mini-Review - Gabriele Vargas; Jefferson Cypriano; Tarcisio Correa; Pedro Leão; Dennis A. Bazylinski; Fernanda Abreu (Molecules, 2018)
Magnetotactic bacteria (MTB) biomineralize magnetosomes, which are defined as intracellular nanocrystals of the magnetic minerals magnetite (Fe3O4) or greigite (Fe3S4) enveloped by a phospholipid bilayer membrane. The synthesis of magnetosomes is controlled by a specific set of genes that encode proteins, some of which are exclusively found in the magnetosome membrane in the cell. Over the past several decades, interest in nanoscale technology (nanotechnology) and biotechnology has increased significantly due to the development and establishment of new commercial, medical and scientific processes and applications that utilize nanomaterials, some of which are biologically derived. One excellent example of a biological nanomaterial that is showing great promise for use in a large number of commercial and medical applications are bacterial magnetite magnetosomes. Unlike chemically-synthesized magnetite nanoparticles, magnetosome magnetite crystals are stable single-magnetic domains and are thus permanently magnetic at ambient temperature, are of high chemical purity, and display a narrow size range and consistent crystal morphology. These physical/chemical features are important in their use in biotechnological and other applications. Applications utilizing magnetite-producing MTB, magnetite magnetosomes and/or magnetosome magnetite crystals include and/or involve bioremediation, cell separation, DNA/antigen recovery or detection, drug delivery, enzyme immobilization, magnetic hyperthermia and contrast enhancement of magnetic resonance imaging. Metric analysis using Scopus and Web of Science databases from 2003 to 2018 showed that applied research involving magnetite from MTB in some form has been focused mainly in biomedical applications, particularly in magnetic hyperthermia and drug delivery.